2010
DOI: 10.1159/000323906
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol – A New Modulator of Neuroglobin Levels in Neurons: Role in Neuroprotection against H<sub>2</sub>O<sub>2</sub>-Induced Toxicity

Abstract: Although discovered in 2000, neuroglobin (Ngb) functions are still uncertain. A contribution to the role played by Ngb in neurons could certainly derive from the identification of Ngb endogenous modulators. Here, we evaluate the possibility that Ngb could be regulated by 17β-estradiol (E2) signaling in both SK-N-BE human neuroblastoma cell line and mouse hippocampal neurons. 1 nM E2 rapidly induced a 300% increase in Ngb levels in both models. The E2 effect was specific, being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 76 publications
7
95
0
Order By: Relevance
“…These results represent the first evidence for steroid hormone modulation of globin levels in cells (104). Recently, it has been reported that Hb is specifically expressed in neurons, its expression being upregulated by erythropoietin and accompanied by enhanced brain oxygenation under physiologic and hypoxic conditions (33).…”
Section: Neuroglobin Levels Are Upregulated By 17b-estradiol Via Erbsupporting
confidence: 51%
See 3 more Smart Citations
“…These results represent the first evidence for steroid hormone modulation of globin levels in cells (104). Recently, it has been reported that Hb is specifically expressed in neurons, its expression being upregulated by erythropoietin and accompanied by enhanced brain oxygenation under physiologic and hypoxic conditions (33).…”
Section: Neuroglobin Levels Are Upregulated By 17b-estradiol Via Erbsupporting
confidence: 51%
“…Although it is possible that the experimental models we used (i.e., neuroblastoma cell line and embryonic mouse hippocampal neurons) do not express P450-aromatase causing the inability of testosterone to modulate Ngb levels, the reported results firmly indicate Ngb as a new E2 target that should be added to the variety of E2-specific actions in the brain (104).…”
Section: Neuroglobin Levels Are Upregulated By 17b-estradiol Via Erbmentioning
confidence: 91%
See 2 more Smart Citations
“…These somewhat 13 contrasting and tissue specific estrogen actions are guaranteed by 14 the differential expression of the two estrogen receptor subtypes 15 (i.e., ERa and ERb) which define the different biological cellular 16 response to hormones [2,43]. In particular, the proliferative and 17 anti-apoptotic effect of 17b-estradiol (E2) in cancer cells is 18 primarily mediated by the ERa activation, whereas ERb seems 19 to oppose ERa actions activating pro-apoptotic cascade 20 [1,26,41,54].…”
Section: Introductionmentioning
confidence: 99%